Some Results On Mathai-Haubold Fuzzy Entropy (European Journal of Pure and Applied Mathematics, 2024)
The concept of entropy, emerged from thermodynamics and statistical mechanics is of fundamental importance in some scientific and technological areas such as communication theory, physics, probability and statistics. Fuzzy entropy is much looked upon concept for measuring fuzzy information. The concept of fuzzy entropy was firstly mentioned by Zadeh way back in 1965 asa measure of fuzziness. In this paper , we introduce Mathai - Haubold fuzzy entropy with the proof of its validity. In addition, the elegant properties are studied of the proposed fuzzy entropy measure.
Keywords: Entropy , Generalized Entropy, Fuzzy Sets, Fuzzy Entropy , Shannon Entropy , Renyi Entropy, Generalized Fuzzy Entropy, Mathai-Haubold Entropy